"Here you feel like it's not taboo": An evaluation of a pediatric hospital-based HIV support group. Issue 4 (1st October 2016) - Muskat, Barbara; Salter, Robyn; Shindler, Simone; Porter, Megan; Bitnun, Ari
ABSTRACT: Developing effective psychosocial support for pediatric HIV patients remains vitally important to address the stigma and treatment demands associated with the condition. This study evaluated hospital clinic groups for pediatric patients living with HIV. An analysis of interviews with 16 group participants, and nine of their parental caregivers indicated that attendees and caregivers found the group instrumental in offering support and challenging stigma associated with HIV. Attendees noted an increase in treatment adherence and feelings of empowerment. Offering the group during hospital clinic appointments was convenient and appreciated. These positive findings offer promise for psychosocial support to pediatric HIV patients.